A Comprehensive Study On Krimi And Its Management Through The Three Fold Principle Of Treatment Of Charaka Samhita - Jha, Neetu; Behera, Nabin Kumar; Meher, Sushil Kumar; Sahoo, Manoj Kumar; Panda, P K (International Research Journal of Ayurveda & Yoga, 2021)
Introduction-. Krimi (worms) is considered as one of the causative factor for Aagantuja Vyadhi. Krimiroga (worm infestations) may interrupt growth and development of person and deteriorate the physical condition and leads to malnutrition, if not treated properly. In Charaka Samhita, three fold principle of treatment is given to manage Krimiroga (worm infestations). This research work has been carried out to assess the treatment principle. Aim and Objective- To assess the three steps treatment principle i.e. Apakarshana (Expulsion of harmful substances through shodhan chikitsa), Prakriti Vighata (counteracting/ modalities) and Nidana Parivarjana (avoiding the cause) depicted by Acharya Charaka. Materials and methods-30 patients were registered from OPD and IPD of Govt. Ayurvedic College & Hospital, Balangir, presented with Subjective parameters; Aruchi (anorexia), Chardi (vomiting), Udarashool (pain in abdomen), Vivarnata (discoloration), Atisara (diarrhoea) and Gudakandu (Anal itching) and Objective parameters; Haemoglobin (Hb gm%), DC, TLC, ESR and Absolute eosinophilic count (AEC). After diagnosis they were adviced for Nidana Parivarjana and trialed with Ayurvedic formulations of Virechana Yoga(Trivrit), which was taken as drug for Apakarshana procedure along with Krimihara Yoga (Shigru beeja, Palasha beeja, Maricha and Vidanga), taken as Prakriti Vighata dravya.The assessment of subjective parameters and objective parameters were evaluated in 0th, 7th and 15th day respectively from the day of initiation in order to find the efficacy of both the trial drugs by statistical Wilcoxon test and paired t-test. Observation and Results- It has been observed that the trial drugs work statistically significant to reduce signs and symptoms that had taken as subjective and objective parameters after 15 days of treatment with p-value<0.05. Discussion and Conclusion- So, it can be concluded from this research work that treatment principle given by Maharshi Charaka for Krimiroga (worm infestations) works effectively. No side effect was noticed during clinical study of three fold treatment principle.